1983
DOI: 10.1002/jso.2930240207
|View full text |Cite
|
Sign up to set email alerts
|

Granular cell tumor of the bronchus coexisting with a bronchogenic adenocarcinoma: A case report

Abstract: A case of endobronchial granular cell tumor and an adenocarcinoma in the same lobe of the lung are presented. A review of the literature documents 2 cases where there was coexistence of a bronchogenic carcinoma and a granular cell tumor. The different theories regarding the origin of granular cell tumors are considered. The treatment of choice would be that indicated for the carcinoma irrespective of the granular cell tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Therefore, a conservative therapeutic approach with no removal and close follow‐up (endoscopy, histologic examination) is recommended, and surgical or endoscopic excision should be restricted to symptomatic patients with large tumors (>1 cm) or with histologic features of malignancy 6,7 . When esophageal GCT coexists with cancer, the treatment of choice should be that indicated for cancer 14 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, a conservative therapeutic approach with no removal and close follow‐up (endoscopy, histologic examination) is recommended, and surgical or endoscopic excision should be restricted to symptomatic patients with large tumors (>1 cm) or with histologic features of malignancy 6,7 . When esophageal GCT coexists with cancer, the treatment of choice should be that indicated for cancer 14 …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the coexistence of GCTs with true malignant neoplasm in the same organ has also been described in the literature. There are reports of the association of esophageal, 17–23 lingual, 24 and laryngeal 25,26 GCTs with squamous cell carcinoma, or bronchial, 14,27 , 28 gastric, 9,29 and mammary 30,31 GCTs with adenocarcinoma, and bronchial GCT with small‐cell carcinoma 32 . Both tumors occurred either metachronously, 17–19 or similarly to the case presented here, synchronously 9,14 , 20,21 , 23–32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible to mistake this alteration of the epithelium for squamous cell carcinoma. An association of GCT with squamous cell carcinoma [20,82] or adenocarcinoma [83,84] has been reported and, while it is an uncommon event, the possibility of an underlying malignancy beneath a mucosal GCT must not be neglected.…”
Section: Light Microscopymentioning
confidence: 99%
“…Strong et al reported that the incidence of this association was 9% [3]. The coexistence of GCT and a true malignant neoplasm in the same organ was described as an association of GCT with squamous cell carcinoma of the esophagus [8-10], tongue,[11] and larynx; [12] and GCT with adenocarcinoma in the bronchi [13], stomach [14], and breast [15]. Two of these cancers arose from the epithelium overlying the GCT [12,14]; however; we could not find any prior report of a GCT colliding with adenocarcinoma in the esophagus.…”
Section: Discussionmentioning
confidence: 99%